2002
DOI: 10.1007/s00428-002-0672-3
|View full text |Cite
|
Sign up to set email alerts
|

A case of salivary gland-type mixed tumor of the lung differentiating toward type II alveolar epithelial cells in glandular components with a literature review

Abstract: Salivary gland-type mixed tumor primarily arising in the lung is extremely rare. We report here a case of this type of tumor that occurred in the periphery of S4 of the right middle lobe in a 74-year-old man. Light-microscopically, this lung tumor, 15x9mm in size, exhibited almost the same features as those of mixed tumor of the salivary gland intermingled with chondromyxoid stroma, glandular component, solid growth pattern of myoepithelial components and well-developed cartilage formation, exhibiting a sharp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…This tumor, occurring in a 74-year-old man, contained glandular areas with type II pneumocytic differentiation (surfactant protein positive) and a solid myoepithelial cell component. 9 This tumor also had chondromyxoid stroma and well-developed areas of cartilage formation, similar to conventional mixed tumor. Cartilage was lacking in the 5 cases of PAM described here.…”
Section: Discussionmentioning
confidence: 92%
“…This tumor, occurring in a 74-year-old man, contained glandular areas with type II pneumocytic differentiation (surfactant protein positive) and a solid myoepithelial cell component. 9 This tumor also had chondromyxoid stroma and well-developed areas of cartilage formation, similar to conventional mixed tumor. Cartilage was lacking in the 5 cases of PAM described here.…”
Section: Discussionmentioning
confidence: 92%
“…In a literature review of 24 cases of salivary gland-type mixed tumor of the lung, Matsumoto et al7 suggested that peripherally developed tumors might be derived from primitive stem cells with the ability to differentiate toward ductal structures, myoepithelium, and chondroid and myxoid matrix components. However, our case is morphologically different from pleomorphic adenoma, and immunohistochemical staining of myoepithelial cells showed positivity for normal myoepithelial cells within glands and negative for the stromal cells, while pleomorphic adenoma shows positivity for the stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…But, it was documented in other salivary gland tumors of the lung, such as salivary gland-type mixed tumors and epithelial-myoepithelial tumors [11-13]. The TTF-1 positive tumor cells were also located at the inner layers of glandular components in these tumors, and were considered as alveolar epithelial differentiation [11-13]. It is indicated that the alveolar epithelial differentiation of glandular epithelia might be a special character in the salivary gland tumors of the lung and should be noted.…”
Section: Discussionmentioning
confidence: 99%